Foreign Residents in Warsaw, 1945–1956 - Kochanowski, Jerzy (Acta Poloniae Historica, 2014)
Although it was not before 1989 that Warsaw gradually became a genuinely multiethnic environment, a group of aliens had inhabited the city in 1945–89. Somewhat paradoxically, the Polish capital city’s foreigner landscape proved to be the most variegated, diverse and vivid in the first post-war decade. The Russians, Germans, Englishmen, Frenchmen, or Italians already residing in Warsaw were joined, as part of post-war voluntary and forced (political-refugee) migration, by nationals of Spain, Greece, Korea, Persia, Yugoslavia, or even Canada. The article shows the ways along which they reached Poland and Warsaw, and the various aspects of everyday life of those aliens: work, assimilation, and political entanglements.